Editorial: Phosphorus chemistry in the interstellar medium and planetary atmospheres - Baptista, Leonardo; Benoit, David; Rivilla, Víctor M.; de Almeida, Amaury A. (Frontiers in Astronomy and Space Sciences, 2026)
Graphical AbstractIllustration of a space-themed concept for phosphorus. A triangular flask filled with orange liquid is in the foreground, surrounded by planets and stars. The element is labeled with its periodic table symbol "P" and atomic number 15. Molecule and test tube graphics are at the bottom.